Green - Gino, Alex (Scholastic Press, 2023)
"Crushes are confusing. Green is very lucky. They've got a supportive dad, friendly neighbors, and good friends. They've figured out a lot of things...but they can't figure out what to do about Ronnie. Ronnie's a boy who's been in Green's class for awhile. He's sweet. Funny. And lately Green's heart has raced a little faster whenever he's around. Green is pretty sure about their own feelings, but when it comes to how Ronnie feels, they have ABSOLUTELY NO IDEA. When Green doesn't get a part in the school musical -- a very untraditional version of The Wizard of Oz -- they join the crew to work alongside Ronnie. Is this a good idea? Green's about to find out..."--